Rett's syndrome in the west of Scotland. Issue 6495 (31st August 1985) - Kerr, A M; Stephenson, J B
Abstract : Nineteen girls with characteristic features of Rett's syndrome, including normal initial development, regression at about 12 months of age, repetitive hand movements, and severe mental handicap were studied. This represents an estimated incidence of one in 30 000 live births (one in 15 000 girls) in the west of Scotland. Although the children were often initially considered to be autistic, they did not conform to this diagnosis as they made good personal contact within the limits of their mental development. The developmental regression was sometimes falsely attributed to vaccination. Each child showed striking involuntary movements and abnormality of tone, varying from hypotonia, which was found only in the youngest, to rigidity, which was common in older girls; this permitted classification into three clinical subtypes. The abnormalities were highly suggestive of an extrapyramidal disorder, and this has implications for further research and possible treatment.